PRAKTIK KEPEMIMPINAN ADAPTIF KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU SEKOLAH DASAR - Andriani Ika Prasanti; Yari Dwikurnianingsih; Herry Sanoto (STKIP Subang, 2026)
This study is grounded in the importance of enhancing teacher professionalism in response to educational changes that are not only technical but also adaptive in nature. Common challenges in primary schools include resistance to change, conventional mindsets, and limited reflective and collaborative professional cultures. This study aims to analyze how the principal’s adaptive leadership practices contribute to improving teacher professionalism. A qualitative approach with a case study design was employed. The research participants consisted of one principal and six teachers selected purposively. Data were collected through in-depth interviews, participatory observations, and document analysis, and were analyzed using thematic techniques involving data reduction, data display, and conclusion drawing. The findings reveal that the implementation of six adaptive leadership behaviors—get on the balcony, identify the adaptive challenge, regulate distress, maintain disciplined attention, give the work back to the people, and protect leadership voices from below—successfully created a dialogical, collaborative, and reflective working environment. These practices contributed to increased pedagogical autonomy, greater willingness to innovate, and strengthened professional culture among teachers. Therefore, adaptive leadership serves as an effective strategy for fostering sustainable teacher professionalism in primary schools.